Increasing hydrogen production efficiency from water electrolysis - Ang, Allan Cheng Yi (2018)
The need for green renewable energy is ever more significant in this present day. As a result, a lot of efforts have been placed in finding cheap and efficient electro catalyst to split water compound to obtain hydrogen gas which is a green renewable energy that can be used in a fuel cell. The chemical redox reaction to split water and obtain hydrogen gas (HER) and oxygen gas (OER) is called water electrolysis. Water electrolysis is a redox reaction whereby both HER and OER will happen simultaneously and are interdependent of each other in the water splitting reaction. In order for OER half reaction to happen, four electrons are required to be given out by two oxygen ions while only two electrons are required to be accepted by two hydrogen ions in order for the HER half reaction to happen. This tells us that more energy is thus needed for OER to happen. As a result, in this report, I aim to improve the energy efficiency of hydrogen generation through improving the OER performance. This report shows how the combination of creating a 3D macroporous structure by electro depositing nickel on nickel foam and creating numerous active grain boundaries by performing lithium intercalation can improve the OER performance of the electro catalyst.